Biomass, yield and competitiveness of maize and bean crops in an association system - Ligarreto-Moreno, Gustavo Adolfo; Arenas-Ochoa, Evelyn Gisela (Revista Ceres, 2023)
Polycultures are of great importance in conventional agriculture in the tropical zone, where they are a sustainable source of food production. In this study, the biomass distribution, crop yield and competition were determined in the maize and bean association. The total dry biomass accumulation of maize plants of the monoculture Simijaca SM(o) was higher than that of beans of monocultures cultivars Iraca IB(o) and Hunza HB(o). In monoculture, cultivar Iraca obtained the highest bean yields reaching 2744.0 kg ha-1 in the municipality of Gama, whereas cultivar Simijaca had the highest yields with a value of 7766.7 kg ha-1. In the association, the best environment was the municipality of Simijaca for the SMxIB treatment, which showed a total yield of 9767.5 kg ha-1. The total land equivalent ratio (LERt) was higher than 3.65, showing the advantage of this association. Additionally, the competitive ratio (CR) of the crops showed the high competition effect between maize and the two bean cultivars. The study generated new knowledge about the genetic resources of maize and climbing beans grown at the same time and in the same place, in the search for sustainable and resilient production.